Synthesis and Magnetic Properties of β‐KVOF312. Issue 6 (23rd January 2014) - Donakowski, Martin D.; Lu, Hongcheng; Gautier, Romain; Saha, Rana; Sundaresan, A.; Poeppelmeier, Kenneth R.
Abstract The potassium vanadium oxide‐fluoride phase β‐KVOF3 was prepared by in‐situ reduction with hydrothermal methods and characterized by single‐crystal X‐ray diffraction and magnetic susceptibility measurements. The compound is orthorhombic [space group Pnma, a = 7.1596(2) Å, b = 7.5392(2) Å, c = 13.0506(4) Å, Z = 8]. The material is structurally similar and isoformulaic to d1 materials of formulae AVOF3 (A+ = alkali metal, ammonium, or organic cation). Magnetic susceptibility data were successfully fit with a Heisenberg chain model. In‐situ reduction of V5+ to V4+ during the hydrothermal reaction conditions was observed in the presence of Br– anions. The role of bromide ions in this reduction is explained and employed to reduce a d0 vanadium species to obtain a material with magnetic behavior.